Preparation method of nitrogen-oxygen doped porous carbon cloth and its application in electrochemical sensing

The preparation of nitrogen-oxygen doped porous carbon cloth through electrochemical etching and nitrogen-oxygen doping treatment solves the problems of complex preparation and unstable performance of traditional electrochemical sensor electrode materials, achieving higher detection sensitivity and lower detection limits.

CN118883680BActive Publication Date: 2025-04-11ZHAOQING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410937461.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-04-11
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

The working electrode materials of existing electrochemical sensors are complexly prepared and expensive, and nanomaterials are prone to agglomeration and fall off, affecting performance reproducibility. The use of non-electrochemically active adhesives leads to a decrease in electrochemically active sites and an increase in resistance.

Method used

The carbon cloth was electrochemically etched and synchronous nitrogen-oxygen doped in sodium nitrate solution by using the constant potential method, and then partial reduction treatment of cyclic voltammetry technology was performed in the phosphate buffer solution to prepare the nitrogen-oxygen doped porous carbon cloth.

Benefits of technology

The specific surface area and electrochemical active sites of the carbon cloth are improved, the adsorption capacity and electrochemical performance of the substance to be tested are enhanced, and the detection sensitivity and lower detection limit are achieved, while reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118883680B_ABST
    Figure CN118883680B_ABST
Patent Text Reader

Abstract

The present invention relates to the preparation of nitrogen-oxygen doped porous carbon cloth and its application in electrochemical sensing. The preparation method comprises: S1: using carbon cloth as a working electrode, a saturated calomel electrode as a reference electrode, and a platinum sheet as an auxiliary electrode to form a three-electrode system, and performing electrochemical etching and synchronous nitrogen-oxygen doping; S2: using cyclic voltammetry technology to electrochemically etch the carbon cloth for partial reduction to obtain a stable nitrogen-oxygen doped porous carbon cloth. The obtained nitrogen-oxygen doped porous carbon cloth is used in the application of a carbendazim electrochemical sensor. The present invention realizes in-situ etching and synchronous nitrogen-oxygen doping of carbon fiber cloth through simple electrochemical treatment. The modified carbon cloth of the present invention is used in a carbendazim electrochemical sensor, which can significantly improve the electrochemical sensing performance of carbendazim, and the detection result is accurate, reliable, highly sensitive, and repeatable, and has the advantages of short detection time and low cost. In addition, the preparation method of the present invention has a simple process, is green and controllable, and is easy to mass produce.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of nitrogen-oxygen doped porous carbon cloth and application of the same in carbendazim detection, belonging to the technical field of material improvement and application thereof. Background Art

[0002] Carbendazim (CBZ) is a systemic benzimidazole fungicide. It is widely used in the cultivation of fruits, vegetables and crops because of its excellent antibacterial effect. CBZ has the characteristics of strong stability, low degradation rate, and can persist in soil, water and food. In recent years, many studies have shown that a certain dose of carbendazim can cause abnormal pathological phenomena such as abnormal reproductive organs, secretory organs, and immune system in animals. Therefore, it is of great significance to establish a rapid analytical method to detect the content of CBZ in food and the environment. At present, the common methods for detecting CBZ mainly include chromatography, spectrophotometry and immunoassay. Although these detection methods can detect the content of carbendazim, they each have their own shortcomings. Chromatography has high accuracy, but the sample pretreatment is complicated and the operation is cumbersome; spectrophotometry has many consumables and poor accuracy; immunoassay antibody preparation is complicated.

[0003] Electrochemical sensors are sensors that use electrochemical principles to convert and amplify signals. They have the advantages of fast response, high sensitivity, and portable instruments, and their applications in the field of analytical detection are increasing. The detection performance of electrochemical sensing devices mainly depends on the working electrode, so the selection of electrode materials is crucial. The working electrodes of traditional electrochemical sensors are generally constructed by directly using solid electrodes such as glassy carbon electrodes (GCE), Pt electrodes, Au electrodes, etc. as working electrodes or as conductive carriers, and modifying electrochemically active nanomaterials such as carbon nanomaterials, transition metals or conductive polymers on their surfaces. However, the above-mentioned modified electrodes are expensive, the electrode preparation process is complicated, and the modified nanomaterials are prone to agglomeration or shedding on the electrode surface, affecting the reproducibility of the electrode performance. In addition, the use of non-electrochemically active adhesives in the electrode preparation process will lead to problems such as reduced electrochemical active sites and increased resistance of the electrode.

[0004] Carbon fiber cloth (CC) is a material woven from carbon fibers, which has the characteristics of light weight, high strength, and corrosion resistance. Carbon cloth is used as the electrode material of electrochemical sensors. It has good self-supporting properties, avoids the use of adhesives, and can adapt to a certain degree of deformation and bending, so that the electrochemical detection device has good stability and reliability under different environments. However, carbon cloth (CC) itself has strong hydrophobicity, low specific surface area, and lacks electrocatalytic active sites, which limits its application in electrochemical sensing. In the modification of CC electrodes, heteroatom doping and / or micromorphology modulation are effective measures to modulate the interface properties of carbon cloth. However, the current modification methods of carbon cloth generally require plasma treatment, high-temperature annealing or hydrothermal treatment, and the process is complicated. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In order to solve the above problems in the prior art, the present invention provides a method for preparing nitrogen-oxygen doped porous carbon cloth and application of the same in electrochemical sensing, specifically in the detection of carbendazim.

[0007] (II) Technical solution

[0008] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0009] A method for preparing nitrogen-oxygen doped porous carbon cloth, characterized in that it comprises the following steps:

[0010] S1: A three-electrode system was formed by using carbon cloth as the working electrode, saturated calomel electrode as the reference electrode, and platinum sheet as the auxiliary electrode. The carbon cloth was electrochemically etched and simultaneously doped with nitrogen and oxygen in a sodium nitrate solution using a constant potential method.

[0011] S2: The electrochemically etched carbon cloth obtained in S1 is partially reduced in a phosphate buffer solution using cyclic voltammetry to remove some unstable groups, thereby obtaining a stable nitrogen-oxygen doped porous carbon cloth.

[0012] In the preparation method as described above, preferably, the constant potential of the constant potential method is 1.8-2.6 V, and the time for electrochemical etching and synchronous nitrogen and oxygen doping is 5-30 minutes.

[0013] Further preferably, the constant potential is 2.0-2.4 V, and the time of electrochemical etching and simultaneous nitrogen and oxygen doping is 5-15 min. More preferably, the constant potential is 2.2 V, and the time of electrochemical etching and simultaneous nitrogen and oxygen doping is 10 min.

[0014] In the preparation method as described above, preferably, in step S1, the concentration of the sodium nitrate solution is 0.5-4 mol / L.

[0015] In the preparation method as described above, preferably, in step S1, the concentration of the sodium nitrate solution is 3 mol / L.

[0016] In the preparation method described above, preferably, in step S1, the area of ​​the carbon cloth working electrode is 0.5×0.5 cm 2 ~2.0×2.0cm 2 .

[0017] In the preparation method described above, preferably, the area of ​​the carbon cloth working electrode is 0.5×0.5 cm 2 .

[0018] In the preparation method as described above, preferably, in step S2, the phosphate buffer solution is a 0.2 mol / L PBS buffer solution (pH=7.0), and the conditions of cyclic voltammetry are a scanning potential range of -0.5 to 0.5 V, a scanning rate of 100 mV / s, and a cycle number of 20.

[0019] The nitrogen-oxygen doped porous carbon cloth prepared by the above-mentioned preparation method is applied in electrochemical detection.

[0020] The nitrogen-oxygen doped porous carbon cloth prepared by the above-mentioned preparation method is used in the electrochemical detection of carbendazim.

[0021] As used above, preferably, the electrochemical detection is an electrochemical sensor composed of the nitrogen-oxygen doped porous carbon cloth obtained by the preparation method described above as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum sheet as the auxiliary electrode.

[0022] As applied above, preferably, the electrochemical detection is performed by differential pulse voltammetry to test electrochemical performance.

[0023] As applied above, preferably, before the differential pulse voltammetry test, the test solution is first added to the electrolyte solution, the test substance is enriched by constant potential, and then the test is performed. The enrichment conditions are voltage 0.5V, enrichment time 900s, and stirring rate 1500r / min; the differential pulse voltammetry parameters are set as follows: initial potential value is 0.4V, termination potential value is 1.1V, potential increase is 0.005V, amplitude is 0.05V, pulse width is 0.06s, pulse period is 0.25s, static time is 0s, and sensitivity value is 1×10 -2 A / V.

[0024] As applied above, preferably, the electrolyte used for the electrochemical detection is a 0.2 mol / L phosphate buffer solution, pH=5-8.

[0025] Further preferably, the pH of the phosphate buffer solution is 7.0.

[0026] The nitrogen-oxygen doped porous carbon cloth obtained by the preparation method described above is used in the preparation of an electrochemical sensor for detecting carbendazim. The peak current response value of the PBS solution standard containing different concentrations of carbendazim is detected by differential pulse voltammetry, and the linear relationship between the carbendazim concentration and the peak current value is obtained. A standard working curve is established, and the content of carbendazim in the sample to be tested can be obtained according to the standard working curve.

[0027] The method of the present invention adopts electrochemical etching and doping treatment to make the carbon fiber obtain a rich porous structure, expose more active sites, and be more conducive to electron and material transfer. Oxygen-containing groups such as carboxyl and hydroxyl groups are introduced on the surface of the carbon cloth to increase the hydrophilicity of the electrode. In addition, the oxygen-containing groups may form hydrogen bonds with the analyte, thereby increasing the adsorption capacity of the carbon fiber to the analyte, so that the analyte is enriched on the carbon cloth, so that it can be detected more sensitively.

[0028] (III) Beneficial effects

[0029] The beneficial effects of the present invention are:

[0030] The present invention provides a method for preparing nitrogen-oxygen doped porous carbon cloth, using constant potential technology, electrochemically oxidizing and etching the carbon cloth in a sodium nitrate solution, and introducing an appropriate amount of nitrogen-containing oxygen groups on the surface of the carbon cloth to prepare nitrogen-oxygen doped porous carbon cloth. The preparation method is simple in process, green and controllable, and easy to scale production. The nitrogen-oxygen doped carbon cloth prepared by the present invention has a rich nanopore structure, effectively improves the specific surface area of ​​the carbon cloth, exposes more active sites, and is conducive to electron and material transfer. In addition, the introduction of nitrogen-oxygen groups is also conducive to enhancing the interaction with the object to be measured, and plays a role as a catalyst in the redox reaction. The nitrogen-oxygen doped porous carbon cloth electrode obtained can be used for application in the detection of carbendazim. The nitrogen-oxygen doped porous carbon cloth is used as a working electrode of an electrochemical sensor, without the need to use an adhesive, and can improve the sensitivity of detection, reduce the detection limit, and reduce costs.

[0031] The invention provides a method for detecting carbendazim by using a nitrogen-oxygen doped porous carbon cloth electrode, wherein the peak current value of a PBS buffer standard containing different concentrations of carbendazim is detected by differential pulse voltammetry, a standard curve is drawn based on the linear relationship between different concentrations of carbendazim and the peak current value, and the content of carbendazim in a sample to be tested can be obtained according to the standard curve. The detection result is accurate and reliable, the detection sensitivity is high, the repeatability is good, and the detection time is short, the cost is low, and the like are also advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The SEM results of N, O-MCC and CC are shown;

[0033] Figure 2XPS spectra, C 1S peaks and N1S peaks of N,O-MCC and CC;

[0034] Figure 3 DPV curves of N,O-MCC and CC in 0.2 M PBS solution (pH=7) without CBZ (dashed line) and with 2 μM CBZ (solid line);

[0035] Figure 4 DPV curves of N,O-MCC electrode detecting PBS solutions containing different concentrations of CBZ;

[0036] Figure 5 This is the standard curve of the N,O-MCC electrode detecting PBS solutions containing different concentrations of CBZ. DETAILED DESCRIPTION

[0037] Through a large number of studies, the present invention uses a constant potential method to electrochemically oxidize and etch commercial carbon cloth in a sodium nitrate solution, so that the carbon cloth has a rich nanopore structure and is doped with nitrogen oxide groups simultaneously; then the etched carbon cloth is partially reduced in a phosphate buffer solution using a cyclic voltammetry technique to remove some unstable groups, thereby obtaining a stable nitrogen oxide-doped porous carbon cloth. By introducing a porous structure on the surface of the carbon cloth, the electrochemical active area of ​​the carbon cloth and the adsorption capacity of the object to be measured are increased. The hydrophilicity of the carbon cloth electrode is improved by using nitrogen-containing and oxygen-containing groups, and the oxygen-containing groups are used to form hydrogen bonds between the objects to be measured, which can further enhance the adsorption capacity of the electrode for the object to be measured, thereby improving the electrochemical performance of the electrode. The electrode is used as an electrochemical sensor for electrochemical detection of carbendazim (CBZ). When exploring the performance of the electrochemical sensor, cyclic voltammetry (CV) and differential pulse voltammetry (DPV) are selected, and finally a high-sensitivity electrochemical sensor for detecting CBZ is prepared.

[0038] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with the accompanying drawings through specific embodiments. If not otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. The reagents used in the following embodiments are all analytically pure and commercially available products can be used, such as carbendazim standard products can be purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The models of the instruments used can be used as follows but are not limited to this: electrochemical analyzer, Shanghai Chenhua Instrument Co., Ltd. CHI1230b; precision AC regulated power supply, Shanghai Zhengxi Electric Technology Co., Ltd. JJW-1000VA; ultrasonic cleaner, Shanghai Kedao Ultrasonic Instrument Co., Ltd. SK220B; dual digital display constant temperature magnetic stirrer, Jintan Chengdong Xinrui Instrument Factory 85-2A; electronic analytical balance, Shimadzu Corporation ATY124; portable pH meter, Shanghai Lichen Instrument Technology Co., Ltd. pH-10; pipette gun, Dalong Xingchuang Experimental Instrument Co., Ltd. TopPette Pipettor.

[0039] Example 1

[0040] 1. Preparation of nitrogen and oxygen doped porous carbon cloth (N,O-MCC)

[0041] S1. Using sodium nitrate solution as electrolyte, electrochemically etch the surface of carbon cloth by constant potential method. Specifically, accurately cut 0.5×1cm 2 The carbon cloth (CC) was used as the working electrode, and the working area was fixed to 0.5 × 0.5 cm 2 , immersed in 20mL of 3mol / L NaNO3 solution, and then set a constant potential for electrochemical oxidation etching and synchronous nitrogen and oxygen doping by ampere-time (it) technology under the electrochemical operation system with three electrodes (CC as working electrode, SCE as reference electrode, platinum sheet as counter electrode). The setting parameters are constant potential 2.2V and oxidation time 600s.

[0042] S2. Electrochemical partial reduction treatment is performed in phosphate (PBS) buffer solution using cyclic voltammetry (CV) technology. Specifically, the carbon cloth that has been electrochemically etched in step (1) is transferred into 20mL of 0.2mol / L PBS (pH=7.0) solution, and 20 cycles of CV scanning are performed in the same three-electrode system with a potential range of -0.5-0.5V and a scan rate of 100mV / s. During the cycle, some unstable groups on the surface can be removed and excess oxygen-containing groups can be reduced, so that the electrochemically etched carbon cloth has higher conductivity and stability, thereby obtaining nitrogen-oxygen doped porous carbon cloth (N,O-MCC).

[0043] S3. Rinse the working electrode in step S2 with distilled water to remove residual electrolyte, dry it in the air, and set it aside.

[0044] 2. Microscopic morphology characterization of nitrogen and oxygen doped porous carbon cloth

[0045] The N,O-MCC and untreated CC obtained above were observed by scanning electron microscope (SEM). Figure 1 As shown in the figure, compared with the smooth surface of the untreated carbon cloth CC, the surface of the N,O-MCC treated by electrochemical etching and activation is rougher and produces a rich nanopore structure, which enables the carbon cloth to obtain a higher specific surface area and more active sites, and is conducive to promoting the transfer of substances and the adsorption of the test object. The interior of each carbon fiber of N,O-MCC still maintains its initial state, so that it can maintain low resistance and good flexibility and self-supporting properties.

[0046] 3. Chemical composition analysis of nitrogen and oxygen doped porous carbon cloth

[0047] The chemical compositions of CC and N,O-MCC were characterized by X-ray photoelectron spectroscopy (XPS). Figure 2 As shown, (a) is the XPS spectra of N,O-MCC and CC, (b) C1S peak of CC; (c) C1S peak of N,O-MCC; (d) N1S peak of N,O-MCC. Figure 2 (a) The results show that the surface of CC is mainly composed of carbon and oxygen elements, with an oxygen content of 4.12%. In comparison, the surface oxygen content of N,O-CC increases and it contains a certain amount of nitrogen elements, with C, N, and O atoms accounting for 77.8%, 18.63%, and 3.57%, respectively, proving that a certain amount of nitroxide groups are doped into the carbon cloth during the electrochemical etching process. Figure 2 (b) and Figure 2 (c) are the C1s XPS spectra of CC and N,O-CC, respectively. Analysis of the C1s XPS spectrum of CC can be fitted into two fitting peaks of C=C / CC bond (284.6eV) and CO bond (285.7eV), and it can be observed that the amount of oxygen-containing groups is relatively low. In the C1s spectrum of N,O-CC, it can be decomposed into five fitting peaks of 284.4eV, 285.6eV, 286.6eV, 287.5eV and 288.8eV, which can be attributed to C=C, C=N / C-OH, CO / CN, C=O, and O=CO, respectively. This shows that a large number of oxygen-containing functional groups such as -OH, -COOH and nitrogen doping are added to the surface of N,O-CC. The oxygen-containing functional groups can increase the hydrophilicity of CC and enhance the adsorption capacity of the analyte. Figure 2The N1s spectrum of (d) can be analyzed and decomposed into four fitting peaks at 398.6eV (pyridine-N), 399.9eV (pyrrole-N), 400.7eV (graphite-N) and 406.5eV (NO). Among them, the NO bond comes from the nitrate adsorbed on the surface of the carbon cloth; pyridine-N, pyrrole-N and graphite-N come from the free radical reaction during the electrochemical oxidation process, and the N atoms are embedded in the carbon lattice through chemical bonds. The ratio of the three is 61.8%:19.0%:19.2%. After peak separation, it can be seen that the nitrogen on the surface of N,O-CC is mainly pyridine-N and graphite-N. They have good chemical stability and certain electron affinity. They can act as catalysts in oxidation reactions, accelerate the reaction rate on the electrode surface, and are conducive to enhancing the electrochemical detection signal.

[0048] Example 2

[0049] This embodiment is a performance test of nitrogen-oxygen doped porous carbon cloth for detecting carbendazim, specifically including:

[0050] The nitrogen-oxygen doped porous carbon cloth (N,O-MCC) prepared in Example 1 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum sheet was used as the auxiliary electrode to form a three-electrode system, that is, an electrochemical sensor was obtained. In each test, 20 mL of 0.2 mol / L PBS buffer solution (pH=7.0) and a certain concentration of carbendazim (CBZ) solution were added to a 50 mL electrolytic cell, and the electrochemical performance was tested by differential pulse voltammetry (DPV).

[0051] It should be noted that before each DPV test on CBZ, the test solution needs to be added to the electrolyte solution and the test substance is enriched using constant potential. The enrichment parameters are set as follows: voltage 0.5V, enrichment time 900s, stirring rate 1500r / min. The basic parameters of the DPV test are set as follows: initial potential value 0.4V, end potential value 1.1V, potential increase 0.005V, amplitude 0.05V, pulse width 0.06s, pulse period 0.25s, static time 0s, sensitivity value 1×10 -2 A / V.

[0052] In comparative case 1, an electrochemical sensor was formed using untreated carbon cloth (CC) as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet as the auxiliary electrode. The carbendazim solution was detected according to the above steps.

[0053] The DPV curves of CC and N,O-MCC in 20 mL 0.2 mol / L PBS solution (pH = 7.0) without and with 2 μmol / L CBZ are shown in Figure 2. Figure 3As shown, a is the DPV baseline of the CC electrode, b is the DPV curve of the CC electrode for 2μmol / L CBZ detection, c is the DPV baseline of the N,O-MCC electrode, and d is the DPV curve of the N,O-MCC electrode for 2μmol / L CBZ detection. It can be seen from the figure that CBZ can undergo electrochemical oxidation reaction on both CC and N,O-MCC, and the oxidation peak potential is about 0.73V. Compared with the blank baseline, the oxidation peak current response value of CBZ on the untreated carbon cloth electrode is very weak, only 4.3μA. However, the oxidation peak current of CBZ on nitrogen and oxygen doped porous carbon cloth is significantly enhanced, up to 1020μA, which is 237 times enhanced than CC.

[0054] From the above results, it can be seen that carbon cloth has better molecular recognition and enrichment ability after electrochemical etching and simultaneous nitrogen and oxygen doping, and greatly improves the sensitivity; nitrogen and oxygen doped porous carbon cloth has a rich porous structure, which makes the carbon cloth have more active sites, introduces oxygen-containing groups such as carboxyl and hydroxyl groups on the surface of the carbon cloth, increases the hydrophilicity of the electrode, and can also form hydrogen bonds with the analyte, thereby increasing the interaction of the carbon cloth with the analyte, and enriches the analyte on the carbon cloth, so that it can be detected more sensitively.

[0055] Example 3

[0056] This example is to optimize the electrochemical etching conditions of nitrogen and oxygen doped porous carbon cloth

[0057] 1. Optimization of oxidation potential

[0058] On the basis of Example 1, other parameters were kept unchanged, only the electrochemical oxidation etching time was changed, and the constant potentials were 1.8 V, 2.0 V, 2.2 V, 2.3 V, and 2.4 V, respectively, for electrochemical oxidation etching treatment to obtain nitrogen and oxygen doped porous carbon cloths with different degrees of oxidation etching, which were marked as N,O-MCC1.8 V, N,O-MCC2.0 V, N,O-MCC2.2 V, N,O-MCC2.4 V, and N,O-MCC2.6 V, respectively.

[0059] According to the method in Example 2, the peak current response of 2 μmol / L CBZ on the above electrode was determined. The oxidation peak current values ​​of N,O-MCC1.8 V, N,O-MCC2.0 V, N,O-MCC2.2 V, N,O-MCC2.4V and N,O-MCC2.6 V were measured to be 630.8 μA, 811.1 μA, 1020 μA, 830.4 μA and 698.3 μA, respectively. The oxidation peak current response value of CBZ shows a trend of first increasing and then decreasing with the increase of oxidation potential. When the oxidation potential is 2.2 V, the CBZ peak current presents a maximum value. Too high oxidation potential may lead to excessive oxidation and etching of carbon cloth, and reduced conductivity.

[0060] 2. Optimization of oxidation time

[0061] On the basis of Example 1, other parameters were kept unchanged, and only the electrochemical oxidation etching time was changed, which was set to 300s and 900s respectively. Electrochemical oxidation etching treatment was performed to obtain N, O-MCC with different oxidation etching degrees, which were marked as N, O-MCC300s and N, O-MCC900s respectively.

[0062] According to the method in Example 2, the oxidation peak current values ​​of 2 μmol / L CBZ in N,O-MCC300s and N,O-MCC900s were measured to be 967.9 μA and 863.8 μA, respectively, which are lower than the N,O-MCC prepared with an oxidation time of 600s in Example 2. Therefore, the preferred oxidation time of 600s is the optimal oxidation time of the present invention.

[0063] 3. Optimization of sodium nitrate solution concentration

[0064] On the basis of Example 1, other parameters were kept unchanged, and only the concentration of NaNO3 solution was changed, which was set to 1.0 mol / L and 4.0 mol / L for electrochemical etching treatment, respectively, to obtain different degrees of oxidation etching, which were marked as N,O-MCC1.0M and N,O-MCC4.0M, respectively.

[0065] According to the method in Example 2, the oxidation peak current values ​​of 2 μmol / L CBZ in N,O-MCC1.0M and N,O-MCC4.0M were measured to be 925.9 μA and 917 μA, respectively, which are slightly lower than the N,O-MCC prepared using 3.0 mol / L NaNO3 solution in Example 2. Therefore, the NaNO3 solution with a preferred concentration of 3 mol / L is the optimal electrolyte of the present invention.

[0066] Example 4 Electrochemical determination of carbendazim (CBZ)

[0067] 1. Standard curve and detection limit

[0068] According to Example 2, DPV detection was performed on CBZ standard solutions of different concentrations, and a standard working curve was drawn based on the relationship between CBZ oxidation peak current and concentration. Specifically, the different concentrations of CBZ were 0.02, 0.05, 0.1, 0.25, 0.5, 1, 2, and 3 μmol / L, respectively. Figure 4 (a) is the DPV curve of different concentrations of CBZ on N,O-MCC. It can be seen that as the concentration of CBZ increases, its oxidation peak current gradually increases. Figure 4(b) It can be seen that the oxidation peak current values ​​of CBZ have a good linear relationship in the range of 0.02-3 μmol / L, and the regression equation is I = 0.473C + 93.78 (R 2 =0.993). The detection limit was 7.3 μmol / L.

[0069] 2. Reproducibility

[0070] According to Example 1, 5 pieces of N,O-MCC were prepared and used as working electrodes of the carbendazim electrochemical sensor. According to Example 2, a CBZ solution with a concentration of 2 μmol / L was measured to obtain peak current values ​​of 5 measurements. The peak current RSD was calculated to be 5.41%, reflecting that the working electrode has good reproducibility.

[0071] 3. The influence of interference

[0072] In the CBZ solution with a concentration of 2μmol / L, 100 times the concentration of interfering substances were added. The interfering substances were inorganic substances such as ammonium chloride, barium chloride, potassium chloride, sodium chloride, and organic substances such as glucose, fructose, citric acid, and vitamin C. Functionalized carbon cloth was used as the working electrode for detection. The anti-interference ability of the sensor was evaluated by comparing the peak current values ​​with and without the addition of interfering substances. It can be seen from the figure that the interference of the above interfering substances with a concentration of 100 times on the CBZ peak current measurement is within ±5%, which shows that the CBZ electrochemical sensor based on N,O-MCC has excellent anti-interference ability.

[0073] Example 5

[0074] This embodiment provides a use of nitrogen-oxygen doped porous carbon cloth. The nitrogen-oxygen doped porous carbon cloth (N,O-MCC) prepared in Example 1 is used in the detection of actual samples containing carbendazim. A spiked recovery experiment of CBZ is performed in a pear juice beverage. The specific steps are as follows:

[0075] (1) Sample spiking: Set three concentrations of low, medium, and high, and add a certain volume of CBZ standard solution to the pear juice beverage sample according to the set concentration gradient to prepare spiked samples with different CBZ concentrations.

[0076] Specifically: take 100μL, 200μL and 400μL of 1mmol / LCBZ standard solution respectively and add it to 10.00g pear juice beverage (Master Kong rock sugar and snow pear) sample, vortex for 2min, and obtain spiked samples with spiked concentrations of 1.92mg / Kg, 3.84mg / Kg and 7.68mg / Kg.

[0077] (2) Sample pretreatment: Place the above 10.00g spiked sample in a 50mL centrifuge tube, accurately transfer 10mL of acetonitrile to the centrifuge tube containing the sample, vortex for 2min, weigh 5g of anhydrous MgSO4 into the centrifuge tube, mix well and let stand for 20min to allow the solution to separate. Transfer to a centrifuge and centrifuge at 4000r / min for 10min, transfer 5mL of the supernatant to a 15mL centrifuge tube containing 1g of anhydrous MgSO4 and 250mg PSA, and centrifuge at 4000r / min for 10min. Pass the supernatant through an organic filter membrane and dilute to 5mL with acetonitrile to obtain the sample solution for subsequent electrochemical determination. Prepare a blank solution while preparing the test solution.

[0078] (3) Preparation of matrix standard working curve: 400 μL of the pre-treated sample blank solution was added with 19.6 mL of 0.2 M PBS solution with pH = 7.0 to obtain 20 mL of blank matrix solution. Different concentrations of CBZ standard solutions were added to the blank matrix solution to prepare the matrix standard working curve according to Example 4.

[0079] (4) Sample solution determination: 400 μL of the actual sample solution prepared above was added to 19.6 mL of PBS buffer solution with a pH of 7.0, and the CBZ in the sample solution was detected using the DPV technology according to Example 2. The oxidation peak current response value of CBZ was read and substituted into the matrix standard working curve to calculate the concentration of CBZ in the PBS buffer solution, and then the CBZ content in the sample was calculated.

[0080] The results are shown in Table 2. The spiked recoveries of CBZ in the actual sample detection were between 81.9% and 91.3%, and the relative standard deviations (RSDs) were between 3.65% and 7.32%. The results show that the prepared N,O-MCC sensor can be used for the quantitative analysis of CBZ in actual samples.

[0081] Table 1

[0082]

[0083] The comparison between the results of N,O-MCC sensor and other sensors for detecting CBZ reported in the previous literature is shown in Table 2. Compared with the reported TiO2 / CPE, NP-Cu / RGO / GCE and MBC@CTS / GCE electrodes, N,O-MCC has a lower detection limit and N,O-CC has a higher sensitivity.

[0084] Table 2

[0085]

[0086] The above results show that N,O-MCC has good electrochemical detection performance for CBZ and the preparation process of N,O-MCC is simple.

[0087] The present invention uses carbon cloth as the working electrode, and compares the performance of the carbon cloth before and after functionalization treatment. It can be learned that electrochemical oxidation treatment can significantly improve the electrochemical sensing performance of the electrode to CBZ. A single-factor optimization experiment was conducted on the experimental conditions for preparing electrochemically oxidized carbon cloth, and it was found that the oxidation etching potential of 2.2V and the oxidation time of 10min were the optimal conditions of the present invention. Compared with the untreated carbon cloth (CC), the nitrogen-oxygen doped porous carbon cloth (N,O-MCC) obtained by the present invention has significantly enhanced electrochemical sensing performance for CBZ, and the current response signal is enhanced by 237 times, and has good reproducibility and anti-interference ability, which can be applied to the detection of CBZ contained in actual samples in real life. The established electrochemical sensor can achieve rapid detection of CBZ.

[0088] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. Application of nitrogen-oxygen doped porous carbon cloth in electrochemical detection of carbendazim, characterized in that: The nitrogen and oxygen doped porous carbon cloth is obtained by the following preparation method: S1: A three-electrode system was formed by using carbon cloth as the working electrode, saturated calomel electrode as the reference electrode, and platinum sheet as the auxiliary electrode. The carbon cloth was electrochemically etched in a sodium nitrate solution using a constant potential method. S2: The electrochemically etched carbon cloth obtained in S1 is partially reduced in a phosphate buffer solution using cyclic voltammetry to obtain a stable nitrogen-oxygen doped porous carbon cloth; In step S1, the constant potential of the constant potential method is 1.8-2.6 V, the concentration of the sodium nitrate solution is 0.5-4 mol / L; the time for electrochemical etching and synchronous nitrogen and oxygen doping is 5-30 minutes.

2. The use according to claim 1, characterized in that In step S1, the area of ​​the carbon cloth working electrode is 0.5×0.5 cm 2 ~2.0×2.0cm 2 .

3. The use according to claim 1, characterized in that In step S2, the phosphate buffer solution is a 0.2 mol / L PBS buffer solution, and its pH is 7.

0. The conditions of cyclic voltammetry are a scanning potential range of -0.5 to 0.5 V, a scanning rate of 100 mV / s, and a cycle number of 20.

4. The use according to claim 1, characterized in that The electrochemical detection uses nitrogen-oxygen doped porous carbon cloth as a working electrode, a saturated calomel electrode as a reference electrode, and a platinum sheet as an auxiliary electrode to form a three-electrode system.

5. The use according to claim 4, characterized in that The electrochemical detection is carried out by differential pulse voltammetry to test the electrochemical performance.

6. The use according to claim 5, characterized in that Before the differential pulse voltammetry test, the solution to be tested was first added to the electrolyte solution, and the constant potential method was used to enrich the analyte. The enrichment conditions were voltage 0.5 V, enrichment time 900 s, and stirring rate 1500 r / min. The differential pulse voltammetry parameters were set as follows: initial potential value 0.4 V, termination potential value 1.1 V, potential increase 0.005 V, amplitude 0.05 V, pulse width 0.06 s, pulse period 0.25 s, static time 0 s, and sensitivity value 1×10 -2 A / V.

7. The use according to claim 5, characterized in that The electrolyte used in the electrochemical detection is a 0.2 mol / L phosphate buffer solution with a pH of 5-8.

Citation Information

Patent Citations

  • Production method and detection method of sensor for detecting inorganic phosphate in fresh water

    CN112067676A

  • FeOOH / CC and nitrite electrochemical sensor thereof and application

    CN115343338A